Integrating Critical Thinking in Project-Based Learning for ESP Classes: An Indonesian Perspective - Dewi Hidayati (Universitas Insan Budi Utomo, 2024)
This study explores the integration of critical thinking (CT) into Project-Based Learning (PjBL) frameworks within English for Specific Purposes (ESP) classes, focusing on Indonesian undergraduate students. By employing a mixed-methods approach, the research investigates the effectiveness of combining CT strategies with PjBL in enhancing students’ language proficiency, problem-solving skills, and engagement. Results indicate that embedding CT components into PjBL significantly improves students’ learning outcomes and prepares them for professional communication challenges in specific fields. The study provides insights into practical applications and pedagogical implications for ESP educators, contributing to the growing body of literature on integrating 21st-century skills into language education.